Processes involved in the functioning of large mammal communities : the role of the African elephant in the ecology of predator-prey relationships - (:unkn) unknown (My University, 2018)
Species can indirectly affect other species and their interactions. The trophic interaction between a predator and its prey can be modified by the presence of a third species either through chain interactions (e.g. successive predation link) either through interaction modification. However, these indirect received few attentions in theorical modelling of food web, and fewer studies tried to explore this phenomenon at the scale of natural complex communities of large mammals. The role of the elephants as modifier of lion’s trophic interaction is explored in the semi-arid woodland savannah ecosystem of Hwange National Park, Zimbabwe. African elephants, as key competitor (male body mass ~ 4000 kg with aggressive behaviour) shape the behaviour of herbivores at waterholes results do not allow to state on the elephant mediation of lion trophic interaction at waterholes. In addition, elephants seem to facilitate the availability of food resources for impalas, possibly by increasing regrowth of shoots by breaking twigs and stem, as these last select habitats used by elephants. However, not effect of facilitation or competition were observed for the other herbivores, which lead to think that elephants do not influence lion trophic interaction in that way. Finally, by altering the physical environment (i.e. engineer species) the elephants affect the visibility and ambush sites for lions in the woody vegetation and ultimately seem to influence the lion kill site selection. This study suggests that indirect effects may act at the community level even if their observation and quantification are difficult in natural communities. Moreover, it supports the observation that it is important to take into account these indirect effects in order to have a thorough understanding and have a better ability to predict the consequences that disruptions may have on the structure and functioning of communities
Keywords: African Research